Associations Between Neuroticism and Executive Function Outcomes: Response Inhibition and Sustained Attention on a Continuous Performance Test. Issue 4 (August 2019) - Crow, Andrew J. D.
There are known relationships between psychopathology, personality, and executive function (EF), though the association between personality and EF, independent of psychopathology, remains understudied. The present study investigated relationships between Five Factor Model personality traits and indices of response inhibition, sustained attention, and response variability on a continuous performance test (CPT) among 50 healthy adults (male = 27, female = 23; M age = 19.9 years, range 18–24 years) of primarily Caucasian descent (58.0%). Participants performed an open-source CPT, the Psychology Experiment Building Language Battery Test of Attentional Vigilance (TOAV), and completed self-ratings of conscientiousness, extraversion, and neuroticism on an inventory developed from the public-domain International Personality Item Pool. After controlling for the influences of age, gender, and other personality traits, neuroticism was significantly associated with faster error reaction time and a higher frequency of multiple responses. Neuroticism was also nominally predictive of more frequent commission errors and faster correct and mean reaction time. The present findings indicate that neuroticism is associated with error-prone behavioral performance on a CPT, suggesting that a propensity to experience negative emotions may manifest as impulsivity and hyperactivity on performance-based measures of EF.